Stability or upheaval? The currency composition of international reserves in the long run - Barry Eichengreen; Livia Chiţu; Arnaud Mehl (European Central Bank (ECB), 2014)
We investigate whether the role of national currencies as international reserves was fundamentally altered by the shift from fixed to flexible exchange rates (what we call the “upheaval hypothesis”), a view that gained adherents following the collapse of the Bretton Woods System. We extend standard data on the currency composition of foreign reserves backward and forward in time to test whether there was a shift in the determinants of reserve currency shares around the breakdown of Bretton Woods. We find evidence in favor of this hypothesis. The effects of inertia and the credibility of policies on international reserve currency choice have become stronger post-Bretton Woods, while those associated with network effects have weakened. We also show that negative policy interventions designed to discourage international use of a currency have been easier to implement than positive interventions to encourage international use. These findings speak to current discussions of the prospects of currencies, like the euro and the renminbi, seen to be seeking to acquire international reserve status and others like the U.S. dollar seeking to preserve it.
Keywords: F30; N20; 330; currency composition; fixed vs. floating exchange rates; international reserves; structural change